1999
DOI: 10.1210/en.140.7.2976
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor Regulation of the Na+/H+ Exchanger Regulatory Factor

Abstract: To better understand the actions of estrogens and antiestrogens in estrogen target cells, we have searched for estrogen-regulated genes in human breast cancer cells, in which the number of genes known to be directly activated by estrogen is quite small. Using differential display RNA methods, we have identified the human homolog of the Na+ -H+ exchanger regulatory factor (NHE-RF), an approximately 50-kDa protein that is also an ezrin-radixin-moesin-binding phosphoprotein, as being under rapid and direct regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
65
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 0 publications
6
65
0
Order By: Relevance
“…The EBP50 gene possesses 13 half-estrogen responsive elements and is overexpressed in response to estrogens in proliferative mammary and endometrial cells. 4,7,9,10,43 Notably, 17␤-estradiol was recently shown to increase the amount of EBP50 in the nuclear fraction of human airway epithelial cells. 44 In addition, cholangiocyte proliferation is regulated by cyclic AMP, 45 which has also been shown to induce an intracellular redistribution of EBP50 in renal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The EBP50 gene possesses 13 half-estrogen responsive elements and is overexpressed in response to estrogens in proliferative mammary and endometrial cells. 4,7,9,10,43 Notably, 17␤-estradiol was recently shown to increase the amount of EBP50 in the nuclear fraction of human airway epithelial cells. 44 In addition, cholangiocyte proliferation is regulated by cyclic AMP, 45 which has also been shown to induce an intracellular redistribution of EBP50 in renal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…The liver is the tissue that displays the highest level of EBP50 expression. 3,4 We previously showed that in rat liver, EBP50 is expressed both in hepatocytes and in cholangiocytes, and that, in the latter, the interaction of cystic fibrosis transmembrane conductance regulator (CFTR) with the PDZ1 domain of EBP50 is required for cAMP-dependent chloride secretion, 5 suggesting an important role of EBP50 in bile secretory functions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…13,22 Previous studies indicate EBP50 messenger RNA (mRNA) and protein levels are high in whole liver, but the cellular expression and distribution of EBP50 and related proteins is unknown. 17,23 Given the known protein-protein interactions of EBP50 and E3KARP, the demonstrated capacity of EBP50 and E3KARP to modulate cAMP-dependent transport in other epithelia and the known stimulatory effect of cAMP on bile formation, the present studies sought to (1) identify the cell type-specific expression and intracellular localization of EBP50 in liver epithelia, (2) compare and contrast these expression patterns with E3KARP, (3) determine the codistribution of ERM proteins with EBP50 and E3KARP, and (4) assess the potential contribution of EBP50 to the cAMP-mediated secretory responses of liver epithelia. The findings indicate that EBP50 is critically localized to play a key role in the organization and regulation of apical transport in bile secretory epithelia and is required for the cAMP-dependent Cl Ϫ secretory response in a cultured cholangiocyte cell model.…”
mentioning
confidence: 99%
“…Estrogen has been shown to enhance NHERF1 expression in MCF-7 cells [10], whereas cortisol increased NHE3 expression in the adult rat kidney [11] and transcriptional activation of the rat NHE3 gene [12]. Moreover, we previously demonstrated that estrogen regulated the developmental increase in placental syncytiotrophoblast levels and change in the localization of the 11β-hydroxysteroid dehydrogenase-1/-2 (11β-HSD-1/2) enzymes [13,14] controlling glucocorticoid metabolism, biochemical and structural events that we proposed underpinned the increase in placental conversion of cortisol to cortisone that occurs between mid and late gestation [15,16].…”
Section: Introductionmentioning
confidence: 99%